2011
DOI: 10.1002/ceat.201100210
|View full text |Cite
|
Sign up to set email alerts
|

Highlighting Important Parameters Often Neglected in Numerical Optimization of Preparative Chromatography

Abstract: When a chromatographic separation process is numerically optimized, a number of input parameters to the column model need to be accurately determined, and the accuracy will affect the reliability of the predicted optimal operational conditions. Furthermore, the numerical accuracy of the solution to the column model will have similar impact. The input parameters holdup volume, injection profiles, and the selection of an algorithm for solving the column model were investigated. Errors in parameters or a numerica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…The reason why the peak shapes of the neutral compounds is more symmetrical than those of ionizable compounds is that their binding constant on these “active” sites is much smaller than that experienced by the ionizable compounds for comparable retention factors. Indeed, the elution of ions requires always a larger amount of water in the eluent than that necessary to elute neutral chemicals .…”
Section: Resultsmentioning
confidence: 99%
“…The reason why the peak shapes of the neutral compounds is more symmetrical than those of ionizable compounds is that their binding constant on these “active” sites is much smaller than that experienced by the ionizable compounds for comparable retention factors. Indeed, the elution of ions requires always a larger amount of water in the eluent than that necessary to elute neutral chemicals .…”
Section: Resultsmentioning
confidence: 99%
“…The rectangular injection profiles have been employed in the calculation for the sake of simplicity. Although the use of real injection profiles would give us slightly more accurate results of the isotherm parameters, this would generate much complexity in the simultaneous fitting of the isotherm parameters because the injection profiles become more eroded with the increasing flow rates and size of the solute . The error generated from the simplified injection profiles is maximum 2–3% , which is acceptable in this case.…”
Section: Modelingmentioning
confidence: 99%
“…Easily reproducible fundamental studies in LC can be done using integrated commercially available system provided that the accuracy of delivered volumetric flow, the temperature control and the system void volumes are properly verified [8,15]. However, in a recent study it was shown that, in order to have reproducible experiments using commercially available system SFC systems, additional sensors are needed to measure the mass flow and the pressure at the column inlet and outlet [9].…”
Section: Introductionmentioning
confidence: 98%